Involving Diaspora and Expatriates as Human Resources in the Health Sector in Nepal - Ghimire J, Mahato, Devkota A, Devkota B (Journal of Nepal Health Research Council, 2013)
Background: Health professional mobility has increased in the recent years and is one of the public health concerns in the developing countries including Nepal. On the other hand, we can’t ignore a positive shift of Nepali diaspora coming back to Nepal for some work related projects. The objective of this study was thus to estimate the number of Nepalese Diaspora and foreign expatriate those are coming to Nepal and explore the ways and process of their engagement in the health sector of Nepal.Methods: Mixed method was used. In total, 13 Key Informant Interviews were conducted at the central level along with record review from professional councils.Results: Nepalese Diasporas mainly come through Diaspora Volunteering Organizations, Non Resident Nepali Association and personal connections to the place of their origin. Nepalese Diasporas have supported as health specialists, health camps and project organizers, trainer and hospital promoters, supplier of equipment including ambulances etc. The Nepalese Diasporas are unrecorded with professional organizations such as NMC and NHPC. As such the real status and results of support from Nepalese Diaspora are not known.Overall, 5,120 foreign medical professionals have served to Nepal through NMC followed by 739 nursing professionals through NNC and 189 paramedical staff through NHPC as of 2012.Conclusions: Systematic information on number and characteristics of the Nepalese Diaspora and their role in the health sector of Nepal is limited. The health professional bodies have some record systems but they lack uniformity and systematic process.